Application of fuzzy controllers in automatic ship motion control systems - Oleksiy Melnyk; Oleg Onishchenko; Svitlana Onyshchenko; Oleksandr Shumylo; Sergiy Volyanskyy; Alla Bondar; Nataliia Cheredarchuk (Institute of Advanced Engineering and Science, 2023)
Automatic ship heading control is a part of the automatic navigation system. It is charged with the task of maintaining the actual ship’s course angle or actual ship’s course without human intervention in accordance with the set course or setting parameter and maintaining this condition under the effect of disturbing influences. Thus, the corrective influence on deviations from a course can be rendered by the position of a rudder or controlling influence that leads to the rotary movement of a vessel around a vertical axis that represents a problem, which can be solved with the use of fuzzy logic. In this paper, we propose to consider the estimation of the efficiency of fuzzy controllers in systems of automatic control of ship movement, obtained by analysis of a method of the formalized record of a logic conclusion and structure of the fuzzy controller. The realization of this allows to carry out effective stabilization of a course angle of a vessel taking into account existing restrictions.